The Effects of Non-Digital Gamification on Grade 11 Students’ Mathematics Achievement and Motivation in Learning Rational Exponents - Worrawat, Arucha; Thongrung, Weerayut; Haarsa, Panyawat (Jurnal Multidisiplin Ibrahimy, 2026)
The study used a quasi-experimental design to examine how non-digital gamified instruction influenced the learning of rational exponents. The objectives of this study were to investigate the effects of non-digital gamification on students’ mathematics achievement and to explore their motivation and engagement in learning rational exponents. The study involved 30 Grade 11 students, and both achievement and motivation in mathematics were examined. Thirty students completed six sessions of gamified mathematics activities. The course modules included gamified components such as games, rewards, peer competition, and achievement goals. The pedagogy was based on Self-Determination Theory and Constructivist Learning Theory. It highlighted autonomy, competence, and involvement. The learning outcome test comprised 15 open-ended items assessing four cognitive domains: knowledge, comprehension, application, and analysis. The data was analysed using a paired-samples t-test. Post-test scores (M = 8.19, SD = 2.80) were significantly higher than pre-test scores (M = 6.44, SD = 3.62), t(29) = 5.99, p < .001. It was an educationally meaningful improvement (effect size, Cohen’s d = 0.54). Qualitative reflections confirmed the quantitative findings. Students reported that the game-based activities increased their interest and attention. They also noted better relationship-building and stronger cooperation during the lessons. Altogether, the results support the notion that classroom gamification provides an effective mechanism for enhancing students’ academic achievement and motivation without relying on digital technology. The findings of this study suggest that non-digital gamification is a useful pedagogical method for advancing mathematics achievement at the upper secondary level.